Long-term video EEG monitoring for diagnosis of psychogenic nonepileptic seizures - Gedzelman ER (Dove Medical Press, 2014)
Evan R Gedzelman, Suzette M LaRoche Department of Neurology, Emory Epilepsy Program, Atlanta, GA, USA Abstract: Psychogenic nonepileptic seizures have long been known by many names. A short list includes hysteroepilepsy, hysterical seizures, pseudoseizures, nonepileptic events, nonepileptic spells, nonepileptic seizures, and psychogenic nonepileptic attacks. These events are typically misdiagnosed for years and are frequently treated as electrographic seizures and epilepsy. These patients experience all the side effects of antiepileptic drugs and none of the benefits. Video electroencephalogram (EEG) monitoring is the gold standard diagnostic test that can make a clear distinction between psychogenic nonepileptic seizures and epilepsy. Video EEG allows us to correctly characterize the patient’s events and therefore properly diagnose and direct management. As a result, years of faulty management and wasted health care dollars can be avoided. Keywords: psychogenic nonepileptic seizures, electroencephalogram, video EEG monitoring, conversion disorder, cognitive behavioral therapy, antiepileptic drugs